Exercise and physical performance in older adults with sarcopenic obesity: A systematic review - Ghiotto, Laura; Muollo, Valentina; Tatangelo, Toni; Schena, Federico; Rossi, Andrea P. (Frontiers in Endocrinology, 2022)
Background: Sarcopenic obesity is characterized by low muscle mass and high body fat; prevalence increases with age, particularly after age 65 years. For this systematic literature review we searched scientific databases for studies on exercise interventions for improving physical performance in adults with sarcopenic obesity; also, we identified potential gaps in clinical practice guidelines that need to be addressed. Methods: We followed the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The databases were searched for studies published through November 2021 that measured physical performance in adults with sarcopenic obesity. Results: Most of the studies applied a strength training protocol in which improvement was noted post-treatment on the Time Chair Rise (TCR), 30-s Chair Stand, and Single Leg Stance (SLS) tests. Discrepancies between the studies were observed when resistance training was combined with or without elastic bands or electromyostimulation, as measured with the Short Physical Performance Battery (SPPB), Physical Performance Test (PPT), Gait Speed, and Timed Up & Go (TUG) test. Post-intervention SPPB, PPT, and gait speed scores showed an increase or maintenance of performance, while TUG test scores were higher according to one study but lower according to another. Conclusions: Engagement in physical exercise, and resistance training in particular, can improve or maintain physical performance in adults with sarcopenic obesity. Study samples should include more men. A future area of focus should be the impact of different types of training (aerobic, power training, combined modalities). Finally, studies with longer intervention periods and follow-up periods are needed to gain a better understanding of the effectiveness of exercise on physical function in adults with sarcopenic obesity.